2018
DOI: 10.3892/or.2018.6928
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PIKfyve using YM201636 suppresses the growth of liver cancer via the induction of autophagy

Abstract: Liver cancer is among the most common types of cancer worldwide. The aim of the present study was to investigate whether the phosphatidylinositol-3-phosphate 5-kinase (PIKfyve) inhibitor, YM201636, exerts anti-proliferative effects on liver cancer. The methods used in the present study included MTT assay, flow cytometry, western blot analysis and an allograft mouse model of liver cancer. The results revealed that YM201636 inhibited the proliferation of HepG2 and Huh-7 cells in a dose-dependent manner. HepG2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…It was reported that EGF and its downstream signalling pathway MEK/ERK or PI3K/ AKT mediated the upregulation of CLDN3 expression and maintain the basic level of claudins (Zhang et al, 2017). Furthermore, YM201636-induced autophagy is dependent upon EGFR overexpression (Hou et al, 2019). Our study is consistent with previous results in terms of YM201636 induced EGFR.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It was reported that EGF and its downstream signalling pathway MEK/ERK or PI3K/ AKT mediated the upregulation of CLDN3 expression and maintain the basic level of claudins (Zhang et al, 2017). Furthermore, YM201636-induced autophagy is dependent upon EGFR overexpression (Hou et al, 2019). Our study is consistent with previous results in terms of YM201636 induced EGFR.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, inhibition of PIKfyve was suggested as a novel target for multiple myeloma. In addition, Hou et al reported that YM201636 possess an inhibitory effect on tumour cell growth via the induction of autophagy in the hepatoma cell lines and in vivo models without any adverse effects (Hou et al, 2019). Our results showed the cytotoxic effects of YM201636 on the NSCLC cell lines and supported previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Apilimod, a potent inhibitor of PIKfyve35, can significantly reduce the entry of SARS-CoV S pseudovirus into 293/hACE2 cells via early endosomes in a dose-dependent manner [49]. Treating 293/ hACE2 cells with another PIKfyve inhibitor, YM201636 [72], also had a similar effect. Moreover, a major downstream effector of PI (3,5)P2, two-pore channel subtype 2 (TPC2) [73], is important for SARS-CoV-2 entry, and tetrandrine (an inhibitor of TPC2) inhibits the activity of SARS-CoV-2 S pseudovirus.…”
Section: Fusion Inhibitorsmentioning
confidence: 94%